If x + y + z = 12 , then find the maximum value of (x – 1) (y – 2) (z – 3).
Share
Lost your password? Please enter your email address. You will receive a link and will create a new password via email.
Please briefly explain why you feel this question should be reported.
Please briefly explain why you feel this answer should be reported.
Please briefly explain why you feel this user should be reported.
To find the maximum value of the product \((x-1)(y-2)(z-3)\) subject to the constraint \(x + y + z = 12\), we can use the method of Lagrange multipliers or directly apply the AM-GM inequality.
Let’s use the AM-GM inequality:
By the Arithmetic Mean-Geometric Mean inequality, for non-negative numbers \(a\), \(b\), and \(c\):
\[ \frac{a + b + c}{3} \geq \sqrt[3]{abc} \]
Equality holds when \(a = b = c\).
Applying this to our problem, we first rewrite \((x-1)(y-2)(z-3)\) in a form that allows us to use the AM-GM inequality.
Let \(a = x – 1\), \(b = y – 2\), and \(c = z – 3\). Then \(a + b + c = x + y + z – 6 = 12 – 6 = 6\).
By AM-GM, we have:
\[ \frac{a + b + c}{3} = \frac{6}{3} = 2 \geq \sqrt[3]{abc} \]
\[ \sqrt[3]{abc} \leq 2 \]
\[ abc \leq 8 \]
So the maximum value of \((x-1)(y-2)(z-3) = abc\) is \(8\), and this maximum is achieved when \(a = b = c = 2\), or equivalently, when \(x = 3\), \(y = 4\), and \(z = 5\).